The effect of labor and capital on transportation logistics' development: The case of Ho Chi Minh, Vietnam - Vu Thi Kim Hanh; Nguyen Hong Nga (Cogent Economics & Finance, 2023)
The objective of this study was to measure eight variables, which included total labor, female labor, trained labor, high school labor, annual capital, asset and long-term capital, state capital, and abroad capital. A second objective was to assess which variables impact labor productivities, capital productivities, and gross domestic product (GDP) growth in four provinces in the southern key economic region in Vietnam. It also assessed how the GDP growth of transportation logistics in Ho Chi Minh (HCM), the GDP growth of HCM, and the GDP growth of Vietnam are impacted by the above eight variables and how they affect each other. The methodology used included the Cobb-Douglas formulation employed in a structural equation modeling (SEM) analysis and five steps of SEM's goodness of fit testing. The software used is Stata 17.0. Some remarkable findings are: Firstly, trained labor had a total and direct positive impact on both goods labor productivity and passenger labor productivity. Secondly, state capital had no effect on goods labor productivity, passenger labor productivity, goods capital productivity, and passenger capital productivity. Thirdly, while trained labor positively affected the growth of Tay Ninh Province, state capital negatively affected the GDP growth of Tien Giang Province. Fourthly, trained labor indirectly negatively affected the GDP growth of transportation logistics in HCM. The implications are that, based on the magnitude of the coefficients, the direction of the effects, the number of variables that affect and are affected, and the magnitude of the effects, we believe that trained labor should be decreased while the GDP growth of transportation logistics should be increased in HCM. State capital had a direct and negative impact on GDP growth in Tien Giang Province; our recommendation is that state capital should be reduced in order to increase GDP growth in Tien Giang Province.
Keywords: 330; capital; Cobb-Douglas; Labor; productivity; SEM; transportation logistics